LEGAL PROTECTION OF CHILD VICTIMS OF ARMED CONFLICT IN THE PERSPECTIVE OF INTERNATIONAL HUMANITARIAN LAW AND ISLAMIC LAW - Astuti, Mirsa; Aksa, Muhammad Faris (Proceeding International Seminar of Islamic Studies, 2024)
This study aims to determine the legal protection of children victims of war according to humanitarian law and Islamic law. The occurrence of armed conflict destroys the rights that the state should give to its people, especially to children. In this case the state is unable to create peaceful conditions for children to exercise their rights.The type of research used is normative legal research, with the type of statutory approach, case approach and conception approach. The source of legal materials used is inseparable from the existing rules in international law by specializing in regulations governing International Humanitarian Law. The technique of collecting legal materials carried out is by exploring normative frameworks and document study techniques using legal materials that discuss international humanitarian law theories, especially the 1949 Geneva Conventions. The results showed that the protection of child victims of armed conflict has been regulated in international humanitarian law in the form of Additional Conventions and Protocols and in Islamic law. Islam teaches noble behavior held in warfare, among other things it is forbidden to kill children.